Computer generated 3D animated holographic stereograms - Reed, Brandon Ian (Department of Mechanical Engineering, 2016)
This thesis describes the process of creating and displaying a computer generated 3D animated holographic stereogram. The objective of the project was to create a computer generated 3-dimensional model and animate it to perform some action using an animation program. This animated object would then be transferred to holographic film in the form of incremental component views of that object, resulting in a holographic stereogram that displays both parallax as well as animation.